2022
DOI: 10.12911/22998993/149609
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of the Generation of Energy in a Biogas CHP System and its Management in a Waste Landfill – Case Study

Abstract: As a waste neutralization facility, the landfill is a kind of bioreactor producing landfill gas or (LFG) -biogas, which should be captured and neutralised for environmental reasons. One of the ways of its utilisation is the combined production of heat and electrical energy in combined heat and power (CHP) cogeneration systems. For that purpose, the assessment of the energy efficiency of a cogeneration unit was undertaken in this work on the basis of the unit performance over the last 5 years. The analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Using statistical tools, Kasinath et al [90] showed the relationship between the parameters of the generated biogas and its rational use, taking into account the environmental aspect. The analysed landfill site as a waste disposal facility is a certain type of bioreactor producing biogas, which, for environmental reasons, should be captured and disposed of [91,92]. Biogas is generally treated as a valuable source of renewable energy produced in anaerobic conditions in a waste landfill site, which, because of the CH 4 content, can be recovered in the form of combined energy [93,94] or ultimately flared to protect the atmosphere from harmful emissions.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Using statistical tools, Kasinath et al [90] showed the relationship between the parameters of the generated biogas and its rational use, taking into account the environmental aspect. The analysed landfill site as a waste disposal facility is a certain type of bioreactor producing biogas, which, for environmental reasons, should be captured and disposed of [91,92]. Biogas is generally treated as a valuable source of renewable energy produced in anaerobic conditions in a waste landfill site, which, because of the CH 4 content, can be recovered in the form of combined energy [93,94] or ultimately flared to protect the atmosphere from harmful emissions.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The availability of such a unit depends primarily on the quality of fuel, which is biogas, which in turn translates into operation indexes of the cogeneration unit. The basic indexes include: the efficiency of electricity and heat generation, the combination index and the savings index of chemical energy of fuel in the form of biogas [Ciuła et al, 2022;Sowa, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the content of the main parameters, which are methane (40-60%) and carbon dioxide 25-45%, as a type of greenhouse gas, it is a potential threat to the environment and people. Therefore, in this case, it is crucial to manage it through controlled intake, treatment and use for energy purposes [5]. Sewage treatment plants in mechanical and biological processes generate waste constituting sewage sludge, which contains significant amounts of biodegradable fractions [6].…”
Section: Introductionmentioning
confidence: 99%